Overview of Pharmaceutical Personnel's Knowledge of Good Compounding Practices in Community Pharmacies - Sri Bintang Sahara Mahaputra Kusuma Negara; Devi Ristian Octavia; Asmaul Fitri Natasia; Andini Suryani (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Compounding is a process of preparing medications tailored to the individual needs of patients by pharmaceutical personnel, due to the limited availability of ready-made drug formulations. Knowledge of drug compounding is essential for pharmaceutical personnel to ensure the availability of quality medications that are safe and effective in achieving therapeutic goals. This study aimed to assess the level of knowledge of pharmaceutical personnel regarding proper compounding practices in pharmacies in Lamongan. The study employed a descriptive design. Data were collected using a questionnaire distributed to pharmacies from February to April 2024. The sampling method used was simple random sampling with a total of 70 respondents. The data were processed and analyzed through editing, coding, scoring, and tabulating. The results showed that out of 70 respondents, the majority (58 respondents; 83%) had good knowledge, 7 respondents (10%) had moderate knowledge, and 5 respondents (7%) had poor knowledge. Knowledge of good compounding practice among pharmaceutical personnel indicated that the highest percentage of correct answers was in the category of compounding definition (97%), while the moderate level of answers was found in the category of compounding aspects (75%). Based on these findings, it can be concluded that pharmaceutical personnel working in pharmacies in Lamongan have, in general, good knowledge of compounding. Keywords: Pharmacy, Compounding, Knowledge, Pharmaceutical Personnel.